Body Dissatisfaction, Importance of Appearance, and Body Appreciation in Men and Women Over the Lifespan - Quittkat, Hannah L.; Hartmann, Andrea S.; Düsing, Rainer; Buhlmann, Ulrike; Vocks, Silja (Frontiers in Psychiatry, 2019)
Body image disturbance is associated with several mental disorders. Previous research on body image has focused mostly on women, largely neglecting body image in men. Moreover, only a small number of studies have conducted gender comparisons of body image over the lifespan and included participants aged 50 years and older. With regard to measurement, body image has often been assessed only in terms of body dissatisfaction, disregarding further aspects such as body appreciation or the importance of appearance. The aim of this cross-sectional study was to explore different aspects of body image in the general German-speaking population and to compare men and women of various ages. Participants completed an online survey comprising questionnaires about body image. Body dissatisfaction, importance of appearance, the number of hours per day participants would invest and the number of years they would sacrifice to achieve their ideal appearance, and body appreciation were assessed and analyzed with respect to gender and age differences. We hypothesized that body dissatisfaction and importance of appearance would be higher in women than in men, that body dissatisfaction would remain stable across age in women, and that importance of appearance would be lower in older women compared to younger women. Body appreciation was predicted to be higher in men than in women. General and generalized linear models were used to examine the impact of age and gender. In line with our hypotheses, body dissatisfaction was higher in women than in men and was unaffected by age in women, and importance of appearance was higher in women than in men. However, only in men did age predict a lower level of the importance of appearance. Compared to men, women stated that they would invest more hours of their lives to achieve their ideal appearance. For both genders, age was a predictor of the number of years participants would sacrifice to achieve their ideal appearance. Contrary to our assumption, body appreciation improved and was higher in women across all ages than in men. The results seem to suggest that men’s and women’s body image are dissimilar and appear to vary across different ages.